Development of Hardness Measurement Procedure for Nanocomposite nc-TiN/a-Si3N4 - Moto, Keba (UI Scholars Hub, 2002)
Hardness of nc-TiN/a-Si3N4 nanocomposites which was determined by using two methods of measurements i. e. depth sensing method and remaining plastic indentation area that were magnified by using SEM (Scanning Electron Microscope) lie in the good agreement. The hardness value is not influenced by the biaxial and residual compressive stress. The measurement of the biaxial stress on the substrate shows a very small value of biaxial stress as well as the constant hardness and crystallite size against annealing temperature. Therefore, the reported hardness value here is the intrinsic value that depend on its microstructure properties.